2013
DOI: 10.1073/pnas.1308627110
|View full text |Cite
|
Sign up to set email alerts
|

Rab GAP cascade regulates dynamics of Ypt6 in the Golgi traffic

Abstract: Significance The Golgi apparatus functions as the central station of membrane traffic in cells. A series of Rab GTPases, which control various steps in membrane traffic, act consecutively during the course of Golgi maturation. Here, we report that Ypt6, a Rab6 homologue in yeast, resides temporarily at the Golgi and dissociates into the cytosol upon arrival of Ypt32, another Rab GTPase functioning in the late Golgi. We have found that Gyp6, a putative GTPase-activating protein for Ypt6, specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
72
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 51 publications
12
72
1
Order By: Relevance
“…In support of the role of Ypt1 in Sec7 recruitment, we observed that Ypt1 levels peak before Sec7 levels, whereas Ypt31/32 levels peak soon after Sec7 levels (Figures 4E,F, S3A,D, Movie S2, and (Suda et al, 2013). We examined three cargos: Kex2, a furin protease that cycles between the TGN and endosomes; Tlg1, a Golgi t-SNARE that also cycles between the TGN and endosomes, and Snc1.…”
Section: Resultssupporting
confidence: 68%
“…In support of the role of Ypt1 in Sec7 recruitment, we observed that Ypt1 levels peak before Sec7 levels, whereas Ypt31/32 levels peak soon after Sec7 levels (Figures 4E,F, S3A,D, Movie S2, and (Suda et al, 2013). We examined three cargos: Kex2, a furin protease that cycles between the TGN and endosomes; Tlg1, a Golgi t-SNARE that also cycles between the TGN and endosomes, and Snc1.…”
Section: Resultssupporting
confidence: 68%
“…For example, although Rab proteins are well-established determinants of membrane identity that regulate membrane trafficking (Barr 2013, Casanova et al 2013, RabC, the A. nidulans homolog of Ypt6/Rab6 regulating endosome-to-Golgi, intra-Golgi and Golgi-to-ER retrograde traffic (Liu and Storrie 2012) partially localizes at both the early and late Golgi entities (Pantazopoulou and Penalva, 2011). A similar localization also has been reported for yeast Ypt6 (Suda et al 2013). Moreover, it seemed that RabC localization is influenced by the distance from the hyphal tip: Close to the tip, where most late Golgi cisternae are found and immediately below the apex, where exocytosis predominates, GFP-RabC localizes mostly in a tubular network containing mCherry-SedV, while away from the tip RabC is in discrete cytoplasmic bodies containing PH OSBP (Pantazopoulou and Penalva 2011).…”
Section: Tlg2 Phsupporting
confidence: 63%
“…21 First, the functionality of mCherry-Ypt1 or GFP-Ypt1 and their level of expression were not shown. 21,24 These 2 criteria are important for making conclusions about Ypt1 localization. Second, co-localization of Ypt1 with other late Golgi markers is needed before a conclusion about its localization to this compartment can be made, especially because YPT1 and SEC7 interact genetically.…”
Section: 25mentioning
confidence: 99%
“…Second, Ypt1 was reported to localize to a late Golgi compartment based on co-localization of fluorescently tagged Ypt1 with Sec7. 21,24 The idea that Ypt1 and TRAPP III regulate multiple transport steps emanating from different origins raised multiple questions: why 2 Ypts, Ypt1 and Ypt31/32, are needed for the regulation of endosome-to-Golgi, what defines Ypt1 specificity if it indeed regulates 3 transport steps in at least 2 cellular locations, and how can one GEF, TRAPP III, regulate transport in 2 different processes? In our most recent paper, we address these puzzling questions and provide support for the Ypt/ Rab compartment specificity model.…”
mentioning
confidence: 99%